2014
DOI: 10.1016/j.energy.2013.10.069
|View full text |Cite
|
Sign up to set email alerts
|

System analysis and optimisation of a Kalina split-cycle for waste heat recovery on large marine diesel engines

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(33 citation statements)
references
References 15 publications
(37 reference statements)
0
33
0
Order By: Relevance
“…On the other hand, the cost of additional equipment like recuperators, separator, mixers and splitters should be compensated by the reduction in the cost from the turbine and the storage system. A more detailed cost study of the KC for geothermal power applications can be found in Campos Rodríguez et al [9] and for waste heat recovery application in Larsen et al [33].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the cost of additional equipment like recuperators, separator, mixers and splitters should be compensated by the reduction in the cost from the turbine and the storage system. A more detailed cost study of the KC for geothermal power applications can be found in Campos Rodríguez et al [9] and for waste heat recovery application in Larsen et al [33].…”
Section: Discussionmentioning
confidence: 99%
“…. [14][15] one course of action of a focal cooling framework appears in Figure 2. The ocean water circuit is comprised of high and low suctions, generally on either side of the apparatus space, suction strainers and a few ocean water pumps.…”
Section: Related Workmentioning
confidence: 99%
“…After these splits, the two rich streams and two of the lean streams are mixed in pairs, and the remaining lean stream is returned to the condenser. This makes it possible to define the outlet conditions for evaporator 1 as saturated vapour for the rich stream and saturated liquid for the lean stream, referred to by Larsen et al [16] as the boiler constraint. The boiler constraint ensures that no temperature change occurs when the streams are mixed after evaporator 1, since the outlet streams are in thermodynamic equilibrium.…”
Section: Comparison To the Kalina Split-cyclementioning
confidence: 99%
“…In the OSC the compositions of the rich and lean streams are not changed from the outlet of the separator to the inlet to the boiler. In the Kalina split-cycle configuration investigated by Larsen et al [16] and Nguyen et al [17], the rich stream is split once (creating two streams) and the lean stream is split twice (creating three streams). After these splits, the two rich streams and two of the lean streams are mixed in pairs, and the remaining lean stream is returned to the condenser.…”
Section: Comparison To the Kalina Split-cyclementioning
confidence: 99%
See 1 more Smart Citation